Antiproliferative Activity of a New Quinazolin-4(3H)-One Derivative via Targeting Aurora Kinase A in Non-Small Cell Lung Cancer - Ji Yun Lee; Huarong Yang; Donghwa Kim; Kay Zin Kyaw; Ruoci Hu; Yanhua Fan; Sang Kook Lee (Pharmaceuticals, 2022)
Non-small cell lung cancer (NSCLC) is the most common lung cancer subtype. Although chemotherapy and targeted therapy are used for the treatment of patients with NSCLC, the survival rate remains very low. Recent findings suggested that aurora kinase A (AKA), a cell cycle regulator, is a potential target for NSCLC therapy. Previously, we reported that a chemical entity of quinazolin-4(3H)-one represents a new template for AKA inhibitors, with antiproliferative activity against cancer cells. A quinazolin-4(3H)-one derivative was further designed and synthesized in order to improve the pharmacokinetic properties and antiproliferation activity against NSCLC cell lines. The derivative, BIQO-19 (Ethyl 6-(4-oxo-3-(pyrimidin-2-ylmethyl)-3,4-dihydroquinazolin-6-yl)imidazo [1,2-a]pyridine-2-carboxylate), exhibited improved solubility and antiproliferative activity in NSCLC cells, including epidermal growth factor receptor–tyrosine kinase inhibitor (EGFR-TKI)-resistant NSCLC cells. BIQO-19 effectively inhibited the growth of the EGFR-TKI-resistant H1975 NSCLC cells, with the suppression of activated AKA (p-AKA) expression in these cells. The inhibition of AKA by BIQO-19 significantly induced G2/M phase arrest and subsequently evoked apoptosis in H1975 cells. In addition, the combination of gefitinib and BIQO-19 exhibited synergistic antiproliferative activity in NSCLC cells. These findings suggest the potential of BIQO-19 as a novel therapeutic agent for restoring the sensitivity of gefitinib in EGFR-TKI-resistant NSCLC cells.